PERBEDAAN HEN DAY PRODUCTION DAN BERAT TELUR AREA DEPAN BELAKANG KANDANG CLOSED HOUSE - Dewi Lestari (AVES: Jurnal Ilmu Peternakan, 2024)
This research was conducted at PT. Phase layer of Jatinom Indah farm, located in Soso village, Gandusari district, Blitar regency. The research began from April 19 to May 19, 2024. The aim of this study was to determine the difference between daily hen production and egg weight in different cage areas, at the front and back of a closed cage. The material used in this study used laying hens aged 40 to 43 weeks, with Isa Brown coloring. The chickens used in the study numbered 128, in the front area 64 chickens and in the rear area 64 chickens. The results showed that the difference in cage area in a closed cage showed a significant effect on daily HDP egg production (P < 0.05), but the difference in cage area in a closed cage was not not significant on egg weight (P > 0.05. Daily). egg production showed a value of 91.63% in the front area and 86.03% in the back area. As for the weight of the eggs, it shows a value of 64.18 grams in the front area and 61.30 grams in the rear area. study, it can be concluded that further research is needed by including FCR calculations to further test the effect on HDP and egg weight.